Fabrication and Characterization of Ferrofluidic-Based Wire-Wound and Wire-Bonded Type Inductor for Continuous RF Tunable Inductor - Fatemeh Bani Torfian Hoveizavi; Nuha Abdul Rhaffor; Sofiyah Sal Hamid; Khairu Anuar Mohamed Zain; Shukri Korakkottil Kunhi Mohd; Mohd Tafir Mustaffa; Asrulnizam Abd Manaf (Applied Sciences, 2020)
This paper reports on the novel implementation of a tunable solenoid inductor using the fluid-based inductance varying technique. The concept utilized material permeability variation that directly modifies self-induced magnetic flow density inside the coil, which in turn creates a variation of the inductance value. The core is formed by a channel which allows the circulation of a liquid through it. The liquid proposed for this technique has ferromagnetic behavior, called ferrofluid, with a magnetic permeability higher than unity. To evaluate the proposed technique, two different types of solenoid inductor were designed, simulated and measured. The two structures are wire-wound and wire bond solenoid inductors. The structures are simulated in a 3D EM analysis tool followed by fabrication, test and measurement. The wire-bonded-based inductor showed a quality factor of 12.7 at 310 MHz, with 81% tuning ratio, by using ferrofluid EMG 901. The wire-wound-based inductor showed that the maximum tuning ratio is 90.6% with quality factor 31.3 at 300 MHz for ferro fluidic EMG 901. The maximum measured tuning ranges were equal to 83.5% and 56.2% for the wire-wound type and the wire-bonded one, respectively. The measurement results for the proposed technique showed a very high tuning range, as well as high quality factor and continuous tunability.